A Model For Developing Entrepreneurship Education In Higher Education Institutions (Heis) Based On The Role Of Entrepreneurship Value Resources For Student Entrepreneurship - Rif’ah Dwi Astuti; Sri Wahyuni; Riyadi Riyadi; Saptianing Saptianing; M Nahar (International Journal of Economics, Business and Innovation Research, 2024)
Entrepreneurship education and training programs have been on the rise in Higher Education Institutions (HEIs) due to the belief that entrepreneurship can be a viable career option for students after graduation. This study aims to develop a model for cultivating entrepreneurial students by focusing on resources that promote entrepreneurship values. The development of this concept is expected to provide opportunities for HEIs to connect the future of graduates with the upcoming needs and challenges.Hypotheses are tested using the data collected from 232SME laundries in Central Java, Indonesia. SEM-AMOS is used to analyze the data. As a mediating variable, entrepreneurship value resources have a positive and significant effect on the relationship between entrepreneurship teacher coachability, entrepreneurial curriculum quality, product value customization, and studententrepreneurial performance. Consequently, entrepreneurship value resources play a critical role in developing entrepreneurship education in HEIs. The concept of entrepreneurship value resources requires further research in different contexts and industries. Besides, the definition of entrepreneurship value resources may vary according to the objects and locations of the study. Keywords: Entrepreneurship Value Resources, Entrepreneurship Teacher Coachability, Entrepreneurial Curriculum Quality, Product Value Customization, Student Entrepreneurial Performance